Pengaruh Variasi Temperatur Artificial Aging Terhadap Kekerasan Aluminium 6061 Daur Ulang - Hartawan, Beny; Marjuni, Teuku; Ansyori, Anang; Prastyo, Adi (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
Recycling is an effective way of utilising scrab ships waste in aluminium 6061. One of the alternative ways of utilisation is by casting. Increasing the hardness of the material after casting is done by artificial aging. The purpose of the study was to determine the material of the castings after the aging process. The research method was sand casting, 450°C heat treatment, quenching with (used) oil cooling media and artificial aging at 190°C with varying resistance times of 1, 5 and 11 hours. The test results after the aging process showed an increase in hardness. The average hardness without heat treatment is 38.6 HRB, then the average hardness of sample AA 1 is 39 HRB. When compared to the average without heat treatment and after aging, it has increased by 1.03%. Then, the average hardness of sample AA 5 is 45 HRB, which is greater than the hardness value of AA 1 hour. Meanwhile, the average hardness of sample AA 11 experienced a decrease in hardness of 40.4 HRB. Structural observations of samples without heat treatment have quite large pores and porosity. The addition of holding time during aging is thought to have no effect on grain size, but changes the grain shape. At the grain boundary of the aluminium matrix, the alloying element Si forms a precipitate that is thought to be a Mg2Si compound. This precipitate is likely to form during the aging process.A maximum 250 word abstract in English in italics with Times New Roman 11 point. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, research methods and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief.